Evaluation Of Pre-Storage Leucoreduction Effect On Pro And Anti-Tumour Cytokines In Whole Blood During Storage - Saman, Srly (2024)
The presence of white blood cells (WBCs) and cytokines in whole blood (WB) during storage may have effect on cancer patients requiring blood transfusions. This study aims to determine the residual of WBCs in WB following leucoreduction and changes in cytokine levels which occur during storage of WB. A total of 31 donors were recruited in this study. Three hundred fifty millilitre of whole blood (WB) was withdrawn from each donor. Half of the blood volume (175 mL) were leucoreduced (LR), while the other half (175 mL) were not leucoreduced and used as a control. Full blood count (FBC) was done using Sysmex KX-21, Japan and residual WBCs subsets were measured using FACSCanto™ II Beckton Dickinson, USA. Cytokines levels from plasma non LR and LR bags on day 0, 10, 20, and 30 days was measured by ELISA method. T-helper (Th) lymphocyte subgroups and gene expression were analysed in the non-LR samples by real-time polymerase chain reaction, respectively. There was a significant difference in the mean of all FBC parameters and residual WBCs subsets between these two groups (p < 0.05). Levels of IL-2 and IL-6 were not detected in both bags during storage. There was a significant difference in TGF-β and IFN-γ between non-LR and LR on day 0 to day 10. TGF-β level showed an increase up to day 30. T-bet, GATA-3, and Foxp3 gene expression were detected in non-LR samples. Leucoreduction demonstrated a significant effect on blood parameters, cytokine levels, and gene expression, emphasizing its importance in WB storage.